The edible gardens of Ethiopia an ethnographic journey into beauty and hunger - Peveri, Valentina, 1978- (Biodiversity in small spaces, 2020)
"Based on prolonged engagement with this "virtuous" plant of southwestern Ethiopia, this book provides a nuanced reading of the Ensete ventricosum (avant-)garden and explores how the life in tiny, diverse, and womanly plots may indeed offers alternative visions of nature, food policy, and conservation efforts"--